2009
DOI: 10.1111/j.1464-410x.2009.08542.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of kidney‐ureter‐bladder abdominal radiography and computed tomography scout films for identifying renal calculi

Abstract: were studied further. Two urology registrars examined the films independently. Location, size and length of stone were recorded. Where there was discordance, the films were examined by an independent radiologist. RESULTSIn all, 108 of 163 patients had both CT and KUB imaging on the same day. Stones were identified in 63% (68/108) of patients with KUB, with a mean length of 4.93 mm. There were 40/108 radiolucent stones subsequently measured on CT, with a mean length of 4.90 mm. Stones were seen on 47% (51/108) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…A very important finding was that all kidney stones visible on the CTI also were visible on the KUB (PPV 100%). This finding corresponds well with previous studies [7][8][9]. In case of CTI negative kidney stones in our data a subsequent KUB would have found it radiopaque in 25% of cases (11/43).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A very important finding was that all kidney stones visible on the CTI also were visible on the KUB (PPV 100%). This finding corresponds well with previous studies [7][8][9]. In case of CTI negative kidney stones in our data a subsequent KUB would have found it radiopaque in 25% of cases (11/43).…”
Section: Discussionsupporting
confidence: 93%
“…In case of CTI negative kidney stones in our data a subsequent KUB would have found it radiopaque in 25% of cases (11/43). One other study showed a similar result (33%) [9] (Fig. 3).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…KUB film has a limited sensitivity for the detection of urolithiasis, but the specificity is acceptable [20]. KUB film could be used for follow-up in 63% of cases [21]. All stones observed on NCCT were also visible on the KUB film, which has been the preferred modality for follow-up imaging if the stone was visible on the initial film.…”
Section: Discussionmentioning
confidence: 99%